SCS eindrapport 6de congres : tewerkstelling in de sport - Colla, Marcel; Dufour, Walter; Van Miert, Karel ([Brussel]: SCS, 1987)
"Het 6de SCS-congres had plaats op 10 jan. 1987 in de VUB te Brussel ; D/98/021"